Towards a Unified Field Theory of Chemistry: Bridging Quantum, Organic, and Biochemical Reactions through a Single Formalism - Barack Ndenga (Publisher, 2025)
Chemistry has historically been divided into distinct sub-disciplines: quantum chemistry, organic chemistry, and biochemistry. While each domain has developed robust predictive models, these approaches remain largely fragmented, resulting in limited capability to predict complex reactions that span multiple scales or domains. This fragmentation slows molecular discovery, hinders rational design of new compounds, and restricts the optimization of reaction pathways. I introduce a Unified Field Theory of Chemistry (UFTC), a single operator-based formalism capable of describing and predicting chemical reactions across quantum, organic, and biochemical systems. The UFTC integrates first-principles quantum mechanics, functional group reaction rules, and enzyme-catalyzed biochemical processes within a coherent mathematical framework. By representing chemical transformations as generalized operators acting on molecular states, I provide consistent predictions of reaction energetics, pathways, and selectivity across diverse chemical domains. I validated the UFTC on a representative set of reactions, including electron transfer in small molecules, aromatic substitution reactions, and enzymatic transformations. The results demonstrate high predictive accuracy compared to experimental data and reveal previously unreported reaction pathways, highlighting the theory’s potential for novel molecular discovery. Furthermore, the UFTC framework is inherently compatible with computational simulations and artificial intelligence, enabling rapid exploration of chemical space, reaction optimization, and green chemistry applications. This unified approach establishes a conceptual and practical foundation for bridging traditionally separate chemical disciplines, accelerating research in drug design, metabolic engineering, and sustainable chemistry, and offering a transformative perspective on the fundamental principles governing chemical reactivity.
This work introduces the Unified Field Theory of Chemistry (UFTC), a novel operator-based framework that bridges quantum, organic, and biochemical chemistry into a single coherent formalism. By integrating quantum mechanical foundations with organic reactivity rules and enzymatic catalysis, the UFTC enables both prediction and optimization of chemical reactions across scales. The methodology relies on universal operators for bond transformations, numerical solutions of Schrödinger-like equations for complex systems, and validation against experimental data. Applications include molecular discovery, green chemistry optimization, biochemical engineering, and integration with AI for high-throughput molecular prediction. Results demonstrate accurate reproduction of electron transfer rates, bond dissociation energies, regioselectivity in organic reactions, and enzyme-catalyzed activation energy reductions, aligning closely with experimental data. The UFTC therefore provides both a conceptual bridge across fragmented domains of chemistry and a practical tool for accelerating discovery in drug design, synthetic biology, and sustainable chemical engineering.